Approaches for Drug Design and Discovery - Karyn Elizabeth; Eri Amalia (Indonesian Journal of Pharmaceutics, 2022)
Drug discovery in general requires high costs and especially a very long time, which is around 11-16 years. This is because drug development must go through a complete series of research processes to obtain comprehensive data. However, in line with the community's need for the availability of quality drugs, having good efficacy and safety, the development of drug development technology using a computing system is carried out. This is in line with the development of science and collaboration between various disciplines. Approaches that can be used for computational drug discovery include Structure-Based Drug Design and Ligand Based Drug Design which are proven to accelerate and increase the possibility of finding new drugs. This article aims to provide an overview of several approaches to drug discovery development, especially the benefits of computational. The data were collected from 28 primary published journals and 28 supporting literatures. This article discusses the two computational methods, especially from the application aspect which is expected to be useful in the field of drug discovery and development to be more efficient in terms of time and cost. The traditional approach to new drug development takes about 11-16 years but using computational methods can shorten the drug discovery stage to 9-13 years. Keywords: Drug Discovery, Ligand Based CADD, Structure-Based CADD